A gossip protocol to support service discovery with heterogeneous ontologies in MANETs - CLARKE, SIOBHAN; CUNNINGHAM, RAYMOND (IEEE, 2007)
Service discovery is vital in enabling interoperability of distributed service-based applications. In mobile ad hoc net-works (MANETs), discovery must cope not only with transient communication but also with an environment in which mobile nodes are autonomous and connectivity is opportunistic. The use of syntactic service interfaces in MANETs requires a priori agreement on interface names, limiting node autonomy and the range of provided services. A more flexible discovery mechanism can be provided with the use of ontologies. Since the use of a single ontology to describe all services also requires a priori agreement on a common semantic representation, a more realistic assumption is the use of heterogeneous ontologies. However, this assumption poses many technical challenges by requiring a mechanism to match the different ontologies and make provided services available to all nodes. This paper presents a model to support such semantic service discovery in MANETs. A core part of the model is the distributed approach to ontology matching and service discovery. We rely on the use of a novel gossip protocol to randomly disseminate ontology concepts, thereby creating a semantic overlay network. We present the gossip protocol and an evaluation demonstrat- ing its scalability and discovery properties.
IEEE International Conference on Wireless and Mobile Computing, Networking and Communications (WiMob) : 3rd : 2007
WiMob 2007
PUBLISHED
Keywords: MANETs; mobile ad hoc net-works; ontologies